School Managers' and Teachers' Opinions on Supervision Policies of the Ministry of National Education - Remzi Burçin Çetin; Büşra Bozanoğlu; Necdet Konan (Anı Publishing, 2019)
The Turkish Ministry of National Education has recently updated education supervision mechanism via the official regulation dated 20.08.2017 and number 30160. Our main motivation for this study is to reveal the opinions of school managers and teachers on supervision policies prior to this latest regulation on education supervision. Thus, a qualitative study has been designed. Thu study group consists of 36 participants working in Malatya during 2017-2018 academic year. The data has been collected by means of a semi structured interviewing form developed by the researchers and analyzed in terms of descriptive analysis technique. Many of the participants have stated that the supervision process should not continue in such way and underlined the fact that the most important factor for reshaping the supervision policies is the "teachers' expectations". In order to organize our education system properly, to build a type of stakeholders' confidence and recover ambiguity; it is essential that the supervision policies of Ministry should be revised prior to experts' and stakeholders' opinions and standardized supervision frameworks should be recreated